2018
DOI: 10.1002/uog.19166
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of fetal heart using 3D ultrasound imaging data

Abstract: Conventional two-dimensional (2D) ultrasonography is the gold standard for diagnosing congenital heart disease (CHD). However, characterization of complex CHD may be limited by 2D imaging methods that lack crucial spatial information, as these images are generated as individual 'slices' without orientation and with a limited field of view lacking depth, and therefore they are not ideal for three-dimensional (3D) modeling and printing. While approximately 90% of 3D printed models of the cardiovascular system ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 5 publications
0
26
0
3
Order By: Relevance
“…In most of these cases, the patients have been children or adults, and only the defective part of the heart was modeled using 3D printing 2-4 . Chen et al reported a case in which 3D printing was used to model a complete normal fetal heart, which demonstrated the feasibility of 3D printing of a small fast-moving fetal anatomical structure without a rest period, based only on 3D ultrasound imaging data 5 . Here, we present two 3D printed multicolor fetal heart models, one of a normal heart and the other of a heart with tetralogy of Fallot, demonstrating the technical feasibility of 3D modeling and 3D printing of normal and abnormal fetal hearts based on ultrasound imaging data.…”
Section: Three-dimensional Printed Multicolor Normal and Abnormal Fetmentioning
confidence: 99%
“…In most of these cases, the patients have been children or adults, and only the defective part of the heart was modeled using 3D printing 2-4 . Chen et al reported a case in which 3D printing was used to model a complete normal fetal heart, which demonstrated the feasibility of 3D printing of a small fast-moving fetal anatomical structure without a rest period, based only on 3D ultrasound imaging data 5 . Here, we present two 3D printed multicolor fetal heart models, one of a normal heart and the other of a heart with tetralogy of Fallot, demonstrating the technical feasibility of 3D modeling and 3D printing of normal and abnormal fetal hearts based on ultrasound imaging data.…”
Section: Three-dimensional Printed Multicolor Normal and Abnormal Fetmentioning
confidence: 99%
“…Combinations of prenatal volume data from US imaging and magnetic resonance imaging (MRI) have also been used. 3D printing using volume US data taken from commercially available US systems was reported only very recently. Advances in consumer electronics and the availability of 3D printing services have now made 3D printing an affordable reality.…”
Section: From Volume To Dicom To Printable Stlmentioning
confidence: 99%
“…Three-dimensional (3D) printing in CHD is gaining increasing interest in the clinical and bioengineering communities alike, considering the breath of its applications. These include medical education, surgical, and catheter-based procedural individualized planning, and manufacturing research for device innovation (13)(14)(15)(16). At present, applications of 3D printing in fetal cardiology are limited, yet the technique is appealing as precise visualization of small structures is essential to achieve a correct diagnosis, even in a very early in pregnancy.…”
Section: Introductionmentioning
confidence: 99%